Atopic dermatitis. Issue 10023 (12th March 2016) - Weidinger, Stephan; Novak, Natalija
Summary: Atopic dermatitis (also known as atopic eczema) is a chronic inflammatory skin disease that is characterised by intense itching and recurrent eczematous lesions. Although it most often starts in infancy and affects two of ten children, it is also highly prevalent in adults. It is the leading non-fatal health burden attributable to skin diseases, inflicts a substantial psychosocial burden on patients and their relatives, and increases the risk of food allergy, asthma, allergic rhinitis, other immune-mediated inflammatory diseases, and mental health disorders. Originally regarded as a childhood disorder mediated by an imbalance towards a T-helper-2 response and exaggerated IgE responses to allergens, it is now recognised as a lifelong disposition with variable clinical manifestations and expressivity, in which defects of the epidermal barrier are central. Present prevention and treatment focus on restoration of epidermal barrier function, which is best achieved through the use of emollients. Topical corticosteroids are still the first-line therapy for acute flares, but they are also used proactively along with topical calcineurin inhibitors to maintain remission. Non-specific immunosuppressive drugs are used in severe refractory cases, but targeted disease-modifying drugs are being developed. We need to improve understanding of the heterogeneity of the disease and its subtypes, the role of atopy and autoimmunity, the mechanisms behind disease-associated itch, and the comparative effectiveness and safety of therapies.